Nitrogen addition decreases methane uptake caused by methanotroph and methanogen imbalances in a Moso bamboo forest - Li, Quan; Peng, Changhui; Zhang, Junbo; Li, Yongfu; Song, Xinzhang (Scientific Reports, 2021)
Abstract Forest soils play an important role in controlling global warming by reducing atmospheric methane (CH 4 ) concentrations. However, little attention has been paid to how nitrogen (N) deposition may alter microorganism communities that are related to the CH 4 cycle or CH 4 oxidation in subtropical forest soils. We investigated the effects of N addition (0, 30, 60, or 90 kg N ha −1 yr −1 ) on soil CH 4 flux and methanotroph and methanogen abundance, diversity, and community structure in a Moso bamboo ( Phyllostachys edulis ) forest in subtropical China. N addition significantly increased methanogen abundance but reduced both methanotroph and methanogen diversity. Methanotroph and methanogen community structures under the N deposition treatments were significantly different from those of the control. In N deposition treatments, the relative abundance of Methanoculleus was significantly lower than that in the control. Soil pH was the key factor regulating the changes in methanotroph and methanogen diversity and community structure. The CH 4 emission rate increased with N addition and was negatively correlated with both methanotroph and methanogen diversity but positively correlated with methanogen abundance. Overall, our results suggested that N deposition can suppress CH 4 uptake by altering methanotroph and methanogen abundance, diversity, and community structure in subtropical Moso bamboo forest soils.

Effects of nitrogen deposition and management practices on leaf litterfall and N and P return in a Moso bamboo forest - Zhang, Junbo; Lv, Jianhua; Li, Quan; Ying, Yeqing; Peng, Changhui; Song, Xinzhang (Biogeochemistry, 2017)

Nitrogen addition increases CO2, CH4, and N2O concentrations of topsoils and subsoils in a subtropical Moso bamboo forest - Lv, Jianhua; Li, Quan; Zhang, Junbo; Li, Yongfu; Peng, Changhui; Song, Xinzhang (CATENA, 2022)

Stumps increased soil respiration in a subtropical Moso bamboo (Phyllostachys edulis) plantation under nitrogen addition - Li, Quan; Ma, Qiuhui; Gao, Jinpei; Zhang, Junbo; Li, Yongfu; Shi, Man; Peng, Changhui; Song, Xinzhang (Agricultural and Forest Meteorology, 2022)

Biochar amendments increase soil organic carbon storage and decrease global warming potentials of soil CH4 and N2O under N addition in a subtropical Moso bamboo plantation - Li, Quan; Cui, Kunkai; Lv, Jianhua; Zhang, Junbo; Peng, Changhui; Li, Yongfu; Gu, Zhikang; Song, Xinzhang (Forest Ecosystems, 2022)

Management scheme influence and nitrogen addition effects on soil CO2, CH4, and N2O fluxes in a Moso bamboo plantation - Zhang, Junbo; Li, Quan; Lv, Jianhua; Peng, Changhui; Gu, Zhikang; Qi, Lianghua; Song, Xuzhong; Song, Xinzhang (Forest Ecosystems, 2021)
Abstract Background It is still not clear whether the effects of N deposition on soil greenhouse gas (GHG) emissions are influenced by plantation management schemes. A field experiment was conducted to investigate the effects of conventional management (CM) versus intensive management (IM), in combination with simulated N deposition levels of control (ambient N deposition), 30 kg N·ha − 1 ·year − 1 (N30, ambient + 30 kg N·ha − 1 ·year − 1 ), 60 kg N·ha − 1 ·year − 1 (N60, ambient + 60 kg N·ha − 1 ·year − 1 ), or 90 kg N·ha − 1 ·year − 1 (N90, ambient + 90 kg N·ha − 1 ·year − 1 ) on soil CO 2 , CH 4 , and N 2 O fluxes. For this, 24 plots were set up in a Moso bamboo ( Phyllostachys edulis ) plantation from January 2013 to December 2015. Gas samples were collected monthly from January 2015 to December 2015. Results Compared with CM, IM significantly increased soil CO 2 emissions and their temperature sensitivity ( Q 10 ) but had no significant effects on soil CH 4 uptake or N 2 O emissions. In the CM plots, N30 and N60 significantly increased soil CO 2 emissions, while N60 and N90 significantly increased soil N 2 O emissions. In the IM plots, N30 and N60 significantly increased soil CO 2 and N 2 O emissions, while N60 and N90 significantly decreased soil CH 4 uptake. Overall, in both CM and IM plots, N30 and N60 significantly increased global warming potentials, whereas N90 did not significantly affect global warming potential. However, N addition significantly decreased the Q 10 value of soil CO 2 emissions under IM but not under CM. Soil microbial biomass carbon was significantly and positively correlated with soil CO 2 and N 2 O emissions but significantly and negatively correlated with soil CH 4 uptake. Conclusion Our results indicate that management scheme effects should be considered when assessing the effect of atmospheric N deposition on GHG emissions in bamboo plantations.

Nitrogen depositions increase soil respiration and decrease temperature sensitivity in a Moso bamboo forest - Li, Quan; Song, Xinzhang; Chang, Scott X.; Peng, Changhui; Xiao, Wenfa; Zhang, Junbo; Xiang, Wenhua; Li, Yan; Wang, Weifeng (Agricultural and Forest Meteorology, 2019)